Віктор Доманицький — український учений, педагог, громадський діяч - Кузьменко, Л.І. (Українська біографістика, 2010)
The publication defi nes the main landmarks of the biography of Viktor Mykolayovych Domanytskyi (January 24, 1893 – March 24, 1962) – a public fi gure, agronomist scientist, sociologist, cooperator, professor of Ukrainian Economic Academy at Podyebrady, rector of Ukrainian Technical and Economic Institute at Regensburg. It describes his stay as an emigrant in Germany from 1922, later – in Czechoslovakia and the USA, his pedagogic and publication activity.